A heat-conducting copper alloy material, a preparation method thereof and application in laser additive manufacturing

By adding specific elements to copper alloys and optimizing the preparation process, the problems of low absorption rate and insufficient thermal conductivity of copper alloys in laser additive manufacturing were solved, and a high-strength and high-thermal-conductivity copper alloy material was achieved, which is suitable for the aerospace and electronic information industries.

CN120519736BActive Publication Date: 2025-10-10GUANGZHOU ZHONGSHAN ADDITIVE TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511028986.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-25
Publication Date
2025-10-10
Estimated Expiration
2045-07-25

AI Technical Summary

Technical Problem

Existing copper alloy materials have problems such as low absorption rate, molten pool sputtering, unfused, spheroidization effect and poor interlayer bonding in laser additive manufacturing, resulting in substandard thermal conductivity, which limits their application in the aerospace and electronic information industries.

Method used

Thermally conductive copper alloy materials are used, and elements such as chromium, iron, manganese, silicon, nickel, cobalt, molybdenum and silver are added to improve material properties through solid solution strengthening, precipitation strengthening and grain boundary strengthening. Powder is prepared through specific melting and atomization processes, and additive manufacturing is carried out in combination with optimized laser scanning parameters.

Benefits of technology

The fluidity and red light absorption rate of copper alloy powder are improved, defects in the additive manufacturing process are reduced, a dense internal structure is formed, thermal conductivity and strength are improved, and high-temperature and high-strength application requirements are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120519736B_ABST
    Figure CN120519736B_ABST
Patent Text Reader

Abstract

The application discloses a heat-conducting copper alloy material and a preparation method and application in laser additive manufacturing thereof. The heat-conducting copper alloy material comprises the following components in mass fraction: 0.05%-0.25% of chromium, 0.001%-0.010% of iron, 0.0001%-0.0010% of manganese, 0.05%-0.10% of silicon, 0.001%-0.005% of nickel, 0.01%-0.10% of cobalt, 0.0001%-0.0005% of molybdenum, 0.0001%-0.0010% of silver, and the balance of copper. The heat-conducting copper alloy powder provided by the application has high roundness, good fluidity, better uniform flow in the additive manufacturing process, helps to form a regular molten pool, reduces the difference between layers, and finally forms a component with few internal defects, thereby providing gain for the heat-conducting effect.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of laser additive manufacturing, in particular to a heat-conducting copper alloy material, a preparation method thereof and application in laser additive manufacturing. BACKGROUND

[0002] Copper and its alloys have an irreplaceable position in the industrial field due to their excellent electrical conductivity, thermal conductivity, corrosion resistance and good machining performance. In particular, in the fields of power engineering, automobile manufacturing and aerospace, the importance of copper alloy materials is increasingly prominent. In recent years, additive manufacturing (AM) has broken through the limitations of traditional manufacturing technology, bringing revolutionary innovation to flexible design and functional integration of products, and is widely used in many fields such as automobiles, medical treatment, aerospace and consumer electronics. However, the high melting point, high thermal conductivity and high reflectivity of copper alloy to laser energy bring challenges to AM technology based on laser or electron beam. In addition, the aerospace and electronic information industries that pursue extreme performance still have growing demand for additive manufacturing of copper alloys. Therefore, it is particularly urgent to study and solve the problems in the AM process of copper alloys.

[0003] In existing research, almost all copper / copper alloy parts are constructed using infrared lasers. However, the absorption rate of copper to infrared laser is low, only about 8%. In order to achieve full melting of copper alloy powder and increase laser energy input, it leads to splashing of the molten pool during scanning, resulting in problems such as incomplete fusion, spheroidization effect (metal powder aggregation into balls), poor interlayer bonding, etc. in the finished product; at the same time, using short-wavelength lasers such as green light and blue light can improve the construction quality of copper alloy, but also brings high equipment cost, which is not conducive to mass production; the application of copper alloy is mainly biased towards heat conduction. Due to a series of problems in the process of laser additive manufacturing of copper alloy, the heat conduction performance of the constructed copper alloy cannot reach the level of traditional forged copper alloy, which is not conducive to the application and promotion of laser additive manufacturing of copper alloy. The above problems need to be solved urgently. SUMMARY

[0004] The present application solves the problems existing in the prior art, and provides a heat-conducting copper alloy material, a preparation method thereof and application in laser additive manufacturing. The heat-conducting copper alloy powder proposed by the present application has high circularity of particle size and good flowability, which can flow uniformly in the additive manufacturing process, help to form a regular molten pool, reduce the difference between layers, and finally form a component with few internal defects, providing gain to the heat conduction effect.

[0005] A first object of the present invention is to provide a thermally conductive copper alloy material comprising the following components, calculated by mass fraction: 0.05%-0.25% chromium, 0.001%-0.010% iron, 0.0001%-0.0010% manganese, 0.05%-0.10% silicon, 0.001%-0.005% nickel, 0.01%-0.10% cobalt, 0.0001%-0.0005% molybdenum, 0.0001%-0.0010% silver, and the balance being copper.

[0006] The various components of the thermal conductive copper alloy material improve the matrix performance through solid solution strengthening, precipitation strengthening, grain boundary strengthening and other methods.

[0007] ①Chromium (Cr)

[0008] Solid solution strengthening: dissolves in the copper matrix to increase strength and hardness.

[0009] Precipitation strengthening: Forming Cr-rich precipitate phase (such as CrCu2) with Cu to enhance high temperature performance.

[0010] ②Iron (Fe)

[0011] Grain refinement: Acting as heterogeneous nucleation points, it refines the molten pool solidification structure during the printing process and reduces the tendency to crack.

[0012] Precipitation strengthening: Formation of nano-scale Fe-Cu precipitation phase to improve strength and wear resistance.

[0013] Improve thermal conductivity / electrical conductivity: Appropriate amount of Fe can reduce the negative impact on copper conductivity.

[0014] ③Manganese (Mn)

[0015] Deoxidizer: Combines with oxygen to form MnO, reduces pores and increases density.

[0016] Solid solution strengthening: significantly improves the strength and hardness of copper while maintaining a certain plasticity.

[0017] Improved processability: suppresses thermal cracking tendency and is suitable for printing complex structures.

[0018] ④ Silicon (Si)

[0019] Fluidity and wettability: reduce the surface tension of the melt, improve the spreadability of the powder during melting, and reduce the spheroidization effect.

[0020] Precipitation strengthening: Forming silicides (such as Cu5Si) or forming eutectic phases with other elements (such as Fe, Ni) to enhance hardness.

[0021] ⑤Nickel (Ni)

[0022] Solid solution strengthening: infinitely soluble with Cu, significantly improving strength while maintaining good toughness.

[0023] Heat resistance: Forms Ni-Cu solid solution (similar structure to Monel alloy), improving high temperature strength and creep resistance.

[0024] ⑥ Cobalt (Co)

[0025] High temperature performance: Forms Co-Cu solid solution, increases recrystallization temperature, and is suitable for high temperature applications.

[0026] Precipitation strengthening: Forms intermetallic compounds (such as CoCr) with Cr, Mo, etc. to enhance hardness and wear resistance.

[0027] ⑦ Molybdenum (Mo)

[0028] Grain refinement: inhibit grain boundary migration and refine the microstructure after printing.

[0029] High temperature strengthening: forming a high melting point Mo-Cu phase (such as MoCu2), improving creep resistance and thermal fatigue performance.

[0030] ⑧ Silver (Ag): Ag has a high solid solubility in copper. Even trace amounts (<0.001%) can be uniformly dissolved, slightly increasing strength without significantly affecting conductivity. Furthermore, Ag tends to concentrate at grain boundaries, reducing grain boundary energy, inhibiting crack growth, and improving ductility.

[0031] The components work synergistically:

[0032] ① Mo-Ag grain boundary synergy: Mo is concentrated at the grain boundary, and Ag fills the grain boundary vacancies, which jointly inhibit grain boundary diffusion and improve high temperature stability.

[0033] ②Si + Ag + Mo synergy: Si solid solution strengthens and Cu5Si precipitates; Ag solid solution strengthens and optimizes conductivity; Mo grain boundary segregation inhibits grain growth. The three effects make the resulting material high in strength, high in conductivity, and has good oxidation resistance.

[0034] ③Ni + Si + Fe synergy: Ni solid solution strengthens, forming Ni-Si precipitation phase; Si eutectic strengthens, improving castability; Co / Fe forms hard intermetallic compounds, such as FeNi3. The three work together to make the resulting material have high strength and corrosion resistance.

[0035] Manganese has a high solid solubility in copper. Its addition significantly increases the number of scattering centers for free electrons in the alloy and may introduce new energy levels into the band structure (such as the Mn³⁺ / Mn²⁺ transition). The energy range of these energy level transitions may extend into the red region. More importantly, manganese readily oxidizes to form dark brown-black or even near-black oxides (such as MnO₂). Even slight oxidation or the formation of manganese-containing compound phases on the alloy surface significantly enhances absorption of visible light, including red light.

[0036] Chromium has limited solid solubility in copper, easily forming fine chromium-rich phases (such as Cr particles). Chromium itself and its oxides (such as Cr2O3, dark green) are very dark in color. These dispersed, dark second-phase particles act as effective light-absorbing centers, significantly increasing light absorption (including red light).

[0037] Iron also has a certain effect on enhancing the red light absorption of a copper matrix. Iron has a very low solid solubility in copper and exists primarily as an iron-rich phase (e.g., Fe particles). These particles themselves are dark (iron-gray), and their oxides (e.g., Fe₂O₃, reddish-brown / rust-colored) also have some red light absorption. When dispersed as a secondary phase, these can increase light absorption and scattering, though the effect is generally less pronounced than that of Mn and Cr.

[0038] Preferably, the thermally conductive copper alloy material comprises the following components, by mass fraction: 0.13%-0.25% chromium, 0.003%-0.010% iron, 0.0001%-0.0010% manganese, 0.050%-0.079% silicon, 0.0017%-0.0050% nickel, 0.02%-0.08% cobalt, 0.0001%-0.0005% molybdenum, 0.0001%-0.0010% silver, and the balance is copper.

[0039] A second object of the present invention is to provide a method for preparing the thermally conductive copper alloy material, comprising the following steps:

[0040] (1) Put the raw materials prepared according to the formula into the smelting container and smelt them under the protection of inert gas to obtain molten metal;

[0041] (2) Atomizing the molten metal obtained in step (1) under the impact of an inert gas to obtain an atomized copper alloy powder; and then sieving the atomized copper alloy powder to obtain the thermal conductive copper alloy material powder. After sieving, a 15-53 μm powder is obtained.

[0042] In the present invention, each raw material preferably uses an intermediate alloy, such as Cu-Cr, Cu-Mn, Cu-Si, etc., which can lower the melting point, accelerate the dissolution of the raw materials, and reduce the burning loss of the raw materials.

[0043] Preferably, the smelting conditions in step (1) are: a smelting temperature of 1450°C-1600°C and a smelting time of 10-30 min. The smelting temperature proposed in the present invention can ensure the dissolution and fluidity of Mo, and is as low as possible to reduce the volatilization of Mn / Ag.

[0044] In step (1), the inert gas is high-purity argon (O2 <5 ppm, dew point <-60°C), which can minimize oxidation and nitridation of the raw materials.

[0045] Preferably, in step (1), the raw materials are added to the smelting vessel in the order of decreasing melting points. The specific order of addition is: refractory / high melting point first, then volatile / easy to oxidize (i.e., Mn, Ag last).

[0046] Preferably, the atomization conditions in step (2) are: atomizing gas pressure of 4.0-8.0 MPa, atomizing gas preheating temperature of 200°C-400°C, and melt superheat of 100°C-250°C. Under these atomization conditions, preheating the gas can prevent premature solidification of the droplets, improve atomization efficiency, improve sphericity, and reduce satellite powder; setting the melt superheat ensures good fluidity of the molten metal and facilitates atomization. Setting the atomizing gas pressure reduces the molten metal particle size, accelerates the cooling rate, and increases the sphericity.

[0047] In step (2), the inert gas atmosphere is an argon atmosphere, and the atomizing gas is high-purity argon or ultra-high-purity nitrogen, which can prevent the metal liquid from being oxidized / nitrided. Argon is preferably used.

[0048] A tightly coupled annular nozzle is used for atomization, which has high atomization efficiency, fine powder with good sphericity, and a draft tube with a diameter of 4-8mm to control the melt flow rate. The draft tube needs to be preheated to >800°C before use.

[0049] The third object of the present invention is to provide an application of the thermally conductive copper alloy material in laser additive manufacturing.

[0050] The present invention also protects a laser additive manufacturing process comprising the following steps:

[0051] (1) Design the model to be processed;

[0052] (2) Powdering the thermal conductive copper alloy material to form a powder layer, and performing laser scanning on the powder layer under the protection of inert gas, wherein the laser power of the laser scanning is 250-350 W, the speed of the laser scanning is 900-950 mm / s, and the scanning interval of the laser scanning is 0.06-0.08 mm; the scanning layer thickness is 25-30 μm, and the spot diameter is 60-80 μm, and additive manufacturing is performed;

[0053] (3) After additive manufacturing, the product is cooled in an inert gas environment, heat treated, and then cooled at room temperature to obtain the target product.

[0054] Preferably, the heat treatment conditions are: heating at a heating rate of 7-9°C / min to 450°C-550°C in the heat treatment container, and keeping the temperature for 2-4 hours.

[0055] Preferably, the laser scanning conditions are as follows: the laser power of the laser scanning is 300 W, the laser scanning speed is 920 mm / s, the scanning pitch of the laser scanning is 0.07 mm; the scanning layer thickness is 30 μm, and the spot diameter is 70 μm.

[0056] Compared with the prior art, the present invention has the following advantages:

[0057] 1. The copper alloy powder proposed in the present invention has high roundness of powder particle size and good fluidity. It flows more evenly during the additive manufacturing process, helps to form a regular molten pool, reduces the differentiation between layers, and finally forms a component with fewer internal defects, which provides a gain in thermal conductivity.

[0058] 2. Elements such as manganese and chromium in the powder matrix are beneficial to improving the powder's absorption rate of red light, so that a good internal morphology can be obtained with lower energy input during the additive manufacturing process, reducing defects such as porosity and unfused materials. The dense internal structure is conducive to heat diffusion, thereby improving thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 These are morphology pictures of the copper alloy powder obtained in Example 1 under an optical microscope, where (a) is a picture of the powder being fully covered, and (b) is a picture of the powder with a small amount of particles. DETAILED DESCRIPTION

[0060] The following examples are provided to further illustrate the present invention, but are not intended to limit the present invention.

[0061] Unless otherwise defined, all technical terms used hereinafter have the same meanings as those generally understood by those skilled in the art. The technical terms used herein are for the purpose of describing specific embodiments only and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the experimental materials and reagents herein are conventional commercial products in the art.

[0062] Example 1

[0063] A thermally conductive copper alloy powder for laser additive manufacturing comprises the following components in percentage by mass: 0.13% Cr, 0.0053% Fe, 0.0005% Mn, 0.079% Si, 0.0017% Ni, 0.02% Co, 0.0003% Mo, 0.0009% Ag, and the remainder being Cu.

[0064] The preparation method thereof comprises the following steps:

[0065] (1) Weighing raw materials: Prepare the raw materials according to the above formula, and use the intermediate alloys Cu-Cr, Cu-Fe, Cu-Mn, Cu-Si, Cu-Ni, Cu-Co, Cu-Mo, and Cu-Ag for compounding;

[0066] (2) Raw material smelting: Put the raw materials into the smelting crucible in descending order of melting point, smelt them at 1450℃ under argon protection, and keep them warm for 30 minutes to obtain molten metal;

[0067] (3) Atomization powder making: The molten metal is atomized under the impact of argon gas (preheated at 200°C, atomizing pressure 4.0 MPa, melt superheat 100°C) to obtain atomized copper alloy powder;

[0068] (4) Screening: The atomized copper alloy powder is screened to obtain thermal conductive copper alloy powder.

[0069] The obtained thermal conductive copper alloy powder was observed under an optical microscope. Figure 1 As shown in the figure, the powder has a high sphericity (0.93), which meets the requirements for additive manufacturing.

[0070] Example 2

[0071] A thermally conductive copper alloy powder for laser additive manufacturing comprises the following components in percentage by mass: 0.19% Cr, 0.003% Fe, 0.0001% Mn, 0.05% Si, 0.003% Ni, 0.05% Co, 0.0001% Mo, 0.001% Ag, and the remainder being Cu.

[0072] The preparation method thereof comprises the following steps:

[0073] (1) Weighing raw materials: Prepare raw materials according to the formula, and use intermediate alloys Cu-Cr, Cu-Fe, Cu-Mn, Cu-Si, Cu-Ni, Cu-Co, Cu-Mo, and Cu-Ag for compounding;

[0074] (2) Raw material smelting: Put the raw materials into the smelting crucible in descending order of melting point, smelt them at 1500℃ under argon protection, keep warm for 20 minutes, and obtain molten metal;

[0075] (3) Atomization powder making: The molten metal is atomized under the impact of inert gas (preheated at 300°C, atomizing gas pressure 6.0 MPa, melt superheat 250°C) to obtain atomized copper alloy powder;

[0076] (4) Screening: The atomized aluminum alloy powder is screened to obtain thermal conductive copper alloy powder.

[0077] Example 3

[0078] A thermally conductive copper alloy powder for laser additive manufacturing comprises the following components in percentage by mass: 0.25% Cr, 0.01% Fe, 0.001% Mn, 0.05% Si, 0.005% Ni, 0.08% Co, 0.0005% Mo, 0.0001% Ag, and the remainder being Cu.

[0079] The preparation method thereof comprises the following steps:

[0080] (1) Weighing raw materials: Prepare raw materials according to the formula, and use intermediate alloys Cu-Cr, Cu-Fe, Cu-Mn, Cu-Si, Cu-Ni, Cu-Co, Cu-Mo, and Cu-Ag for compounding;

[0081] (2) Raw material smelting: Put the raw materials into the smelting crucible in descending order of melting point, smelt them at 1550℃ under argon protection, keep warm for 10 minutes, and obtain molten metal;

[0082] (3) Atomization powder making: The molten metal is atomized under the impact of inert gas (preheated at 400°C, atomizing gas pressure 8.0 MPa, melt superheat 250°C) to obtain atomized copper alloy powder;

[0083] (4) Screening: The atomized copper alloy powder is screened to obtain thermal conductive copper alloy powder.

[0084] Comparative Example 1

[0085] The method is the same as Example 2, except that: during the raw material smelting stage, raw materials with lower melting points are added earlier.

[0086] Comparative Example 2

[0087] The same as Example 3, except that: no mesophase alloy is used as a compound raw material, and pure component raw materials are directly used.

[0088] Comparative Example 3

[0089] The same as Example 1, except that the mass percentage of each component is: Cr: 0.13%, Fe: 0.0053%, Si: 0.079%, Ni: 0.0017%, Co: 0.02%, Mo: 0.0003%, Ag: 0.0009%, and the rest is Cu.

[0090] Comparative Example 4

[0091] The same as Example 1, except that the mass percentage of each component is: Cr: 0.13%, Mn: 0.0005%, Si: 0.079%, Ni: 0.0017%, Co: 0.02%, Mo: 0.0003%, Ag: 0.0009%, and the rest is Cu.

[0092] Comparative Example 5

[0093] The same as Example 1, except that the mass percentage of each component is: Fe: 0.0053%, Mn: 0.0005%, Si: 0.079%, Ni: 0.0017%, Co: 0.02%, Mo: 0.0003%, Ag: 0.0009%, and the rest is Cu.

[0094] Comparative Example 6

[0095] The same as Example 1, except that the mass percentage of each component is: Cr: 0.13%, Fe: 0.0053%, Mn: 0.0005%, Si: 0.079%, Ni: 0.0017%, Co: 0.02%, Mo: 0.0003%, and the rest is Cu.

[0096] Comparative Example 7

[0097] The same as Example 1, except that the mass percentage of each component is: Cr: 0.13%, Fe: 0.0053%, Mn: 0.0005%, Si: 0.079%, Ni: 0.0017%, Co: 0.02%, Ag: 0.0009%, and the rest is Cu.

[0098] Comparative Example 8

[0099] The same as Example 1, except that the mass percentage of each component is: Cr: 0.13%, Fe: 0.0053%, Mn: 0.0005%, Ni: 0.0017%, Co: 0.02%, Mo: 0.0003%, Ag: 0.0009%, and the rest is Cu.

[0100] Comparative Example 9

[0101] The same as Example 1, except that the mass percentage of each component is: Cr: 0.13%, Fe: 0.0053%, Mn: 0.0005%, Si: 0.079%, Co: 0.02%, Mo: 0.0003%, Ag: 0.0009%, and the rest is Cu.

[0102] The materials obtained in Examples 1-3 and Comparative Examples 1-9 were tested.

[0103] 1. Tensile strength test: The test method is ASTM E8 / E8M standard, which tests the room temperature tensile properties of standard tensile rods. The specific test steps are as follows:

[0104] (1) Specimen type: Circular specimen with a gauge diameter of 6.25 mm and a clamping end diameter of 10 mm.

[0105] (2) Specimen size: Gauge length: For specimens with a diameter of 6.25 mm, the gauge length L0 = 25 mm.

[0106] (3) Test equipment

[0107] Universal testing machine: Meets ASTM E4 calibration requirements.

[0108] Extensometer: Used to precisely measure strain with an accuracy of ±1%.

[0109] Clamp: To prevent specimen from sliding, threaded clamp.

[0110] (4) Sample measurement

[0111] Measure the original dimensions of the specimen (diameter / width, thickness) and calculate the cross-sectional area (A0).

[0112] Mark the gauge segments (by dashing or dotting).

[0113] (5) Clamping the specimen: Ensure that the specimen axis is consistent with the loading direction of the testing machine, avoid eccentric loading, and apply a slight preload (<1% of the expected maximum force).

[0114] (6) Set test parameters

[0115] Strain Rate:

[0116] Elastic stage (before yield point): 0.005 ~ 0.01 mm / min (ASTM E8 recommendation).

[0117] Plastic stage (after Yield Point): can be increased to 0.05 ~ 0.1 mm / min.

[0118] Data acquisition frequency: ≥ 10 Hz to ensure the capture of the yield point.

[0119] (7) Conduct tensile test

[0120] Elastic stage: Record the stress-strain curve until the yield point.

[0121] Plastic stage: Loading continues until the specimen breaks.

[0122] After fracture: measure the gage length after fracture (Lf) and calculate the elongation after fracture (%Elongation).

[0123] 2. Prepare the powder into the target product and test its thermal conductivity using the laser flash method.

[0124] The preparation of the target product comprises the following steps:

[0125] (1) Design the model to be processed (taking a 20*20*20 mm square block as an example);

[0126] (2) The thermally conductive copper alloy materials obtained in Examples 1-3 and Comparative Examples 1-9 were powdered to form a powder layer. Under the protection of inert gas, the powder layer was laser scanned. The laser power of the laser scanning was 320 W, the laser scanning speed was 850 mm / s, and the scanning interval of the laser scanning was 0.09 mm. The scanning layer thickness was 30 μm, and the spot diameter was 75 μm. Additive manufacturing was performed. After additive manufacturing, the powder layer was cooled in an argon gas environment and then heat-treated (in a vacuum heat treatment furnace, heated to 500°C at a heating rate of 8°C / min and kept warm for 3 h). Then, the powder layer was filled with argon and cooled to room temperature to obtain the target product.

[0127] Laser Flash Method Principle: Irradiate the back of the sample with a laser pulse, measure the temperature rise curve on the front, calculate the thermal diffusion coefficient (α), and combine the specific heat capacity (Cp) and density (ρ) to obtain λ = α·Cp·ρ.

[0128] Standard: ASTM E1461: Standard Procedure for Laser Flash Method.

[0129] Testing process:

[0130] 1. Sample preparation: Size: 12 mm diameter, 3 mm thickness disc.

[0131] Surface treatment: Spraying graphite layer to improve laser absorption and infrared emissivity.

[0132] 2. Equipment calibration: Use standard reference materials (such as pure copper) to calibrate the instrument. Set parameters such as laser energy and sampling frequency.

[0133] 3. Test steps:

[0134] Place the sample in the sample holder, ensuring alignment with the detector.

[0135] Emit a laser pulse (duration of about 0.1–1 ms) and record the backside temperature rise curve.

[0136] The temperature rise curve was fitted by software and the thermal diffusion coefficient (α) was calculated.

[0137] The thermal conductivity λ was calculated in combination with the specific heat capacity (Cp) and the density (p) measured by DSC.

[0138] 4. Data processing

[0139] The test was repeated 3-5 times to obtain an average value.

[0140] Correct the heat loss effect (such as Cowan model or radiation correction).

[0141] The test results are shown in Table 1 below:

[0142] Table 1

[0143]

[0144] From Table 1, it can be seen that in Comparative Example 1, the lower the melting point of the raw material, the earlier it is put in, resulting in volatilization of the raw material with low melting point, and the copper alloy powder obtained has low roundness and poor flowability, and the material strength is much lower than that of Example 2. In Comparative Example 2, the use of pure component raw materials increases the melting point, reduces the dissolution rate of the raw material, and increases the loss of the raw material, and the thermal conductivity of the copper alloy powder obtained is much lower than that of Example 3. Comparative Examples 3-5 do not add manganese, iron or chromium elements, and the material strength and thermal conductivity of the copper alloy powder obtained are poorer than those of Example 1. In Example 1, the chromium, iron and manganese elements jointly act to obtain a copper alloy powder with much higher thermal conductivity and strength than Comparative Examples 3-5. Comparative Examples 6-8 do not add silver, molybdenum or silicon elements, and the material performance obtained is much lower than that of Example 1. The joint action of silver, molybdenum and silicon elements makes the material have high strength and high thermal conductivity. The thermal conductivity copper alloy materials obtained in Examples 1-3 have good red light absorption capacity, and the copper alloy parts constructed using red light have good thermal conductivity and strength, and do not need to be printed using green light, which can meet the requirements for additive manufacturing. The thermal conductivity copper alloy powder has high particle size roundness and good flowability, which is beneficial to uniform flow in the additive manufacturing process, helps to form a regular molten pool, reduces the difference between layers, and finally forms a component with few internal defects.

[0145] The above description of the embodiments is only used to help understand the technical solutions of the present application and its core idea. It should be pointed out that for those skilled in the art, without departing from the principles of the present application, some improvements and modifications can be made to the present application, and these improvements and modifications also fall within the protection scope of the claims of the present application.

Claims

1. A thermally conductive copper alloy material, characterized in that: Calculated by mass fraction, it includes the following components: chromium 0.05%-0.25%, iron 0.001%-0.010%, manganese 0.0001%-0.0010%, silicon 0.05%-0.10%, nickel 0.001%-0.005%, cobalt 0.01%-0.10%, molybdenum 0.0001%-0.0005%, silver 0.0001%-0.0010%, and the balance is copper; The method for preparing the thermally conductive copper alloy material comprises the following steps: (1) Put the raw materials prepared according to the formula into the melting container, and melt them under the protection of inert gas to obtain molten metal. The raw materials use intermediate alloys and are put into the melting container in the order of decreasing melting points; (2) The molten metal obtained in step (1) is atomized under the impact of an inert gas to obtain an atomized copper alloy powder; and then the atomized copper alloy powder is sieved to obtain the thermal conductive copper alloy material powder.

2. The thermally conductive copper alloy material according to claim 1, characterized in that: Calculated by mass, it includes the following components: chromium 0.13%-0.25%, iron 0.003%-0.010%, manganese 0.0001%-0.0010%, silicon 0.050%-0.079%, nickel 0.0017%-0.0050%, cobalt 0.02%-0.08%, molybdenum 0.0001%-0.0005%, silver 0.0001%-0.0010%, and the balance is copper.

3. The thermally conductive copper alloy material according to claim 1, characterized in that: The smelting conditions of step (1) are: smelting temperature 1450°C-1600°C, smelting time 10-30 min.

4. The thermally conductive copper alloy material according to claim 1, characterized in that: The atomization conditions in step (2) are: atomizing gas pressure 4.0-8.0 MPa, atomizing gas preheating temperature 200°C-400°C, and melt superheat 100°C-250°C.

5. Use of the thermally conductive copper alloy material according to claim 1 or 2 in laser additive manufacturing.

6. A laser additive manufacturing process, characterized in that: The steps include: (1) Design the model to be processed; (2) The thermal conductive copper alloy material according to claim 1 or 2 is powdered to form a powder layer, and the powder layer is laser scanned under the protection of an inert gas, with a laser power of 250-350 W, a laser scanning speed of 900-950 mm / s, and a scanning interval of 0.06-0.08 mm; the scanning layer thickness is 25-30 μm, and the spot diameter is 60-80 μm, for additive manufacturing; (3) After additive manufacturing, the material is cooled in an inert gas environment, heat treated, and then cooled at room temperature to obtain the target product.

7. The laser additive manufacturing process according to claim 6, characterized in that: The heat treatment conditions are as follows: heating the heat treatment container to 450°C-550°C at a heating rate of 7-9°C / min and keeping the temperature for 2-4 hours.

8. The laser additive manufacturing process according to claim 6, characterized in that: The laser scanning conditions are as follows: the laser power of the laser scanning is 300 W, the laser scanning speed is 920 mm / s, the scanning pitch of the laser scanning is 0.07 mm, the scanning layer thickness is 30 μm, and the spot diameter is 70 μm.

Citation Information

Patent Citations

  • Copper alloy preparation method for improving electric conductivity and strength

    CN115570149A

  • Silver containing copper alloy

    US20020039542A1